Apoptosis is involved in paraoxon-induced histological changes in rat cerebellum. (2nd November 2022) - Zare, Zohreh; Zarbakhsh, Sam; Mashhadban, Shamim; Moradgholi, Afshin; Mohammadi, Moslem
Abstract: Acute toxicity of organophosphorus compounds is primarily caused by inhibition of acetylcholinesterase (AChE) at cholinergic synapses. The current study was designed to investigate the effects of paraoxon on histological changes as well as the role of mitochondrion-dependent apoptosis in causing this damage in the rat cerebellum. Adult male Wistar rats were intraperitoneally injected with paraoxon at 0.3, 0.7, or 1 mg/kg. Control animals were injected with corn oil as a vehicle. At 14 or 28 days after intoxication, histological changes and alterations in the expression of apoptosis-related proteins, including Bax, Bcl-2, and caspase-3, were investigated in the cerebellum using cresyl violet staining and western blotting, respectively. Findings showed the decreased thickness of both molecular and granular layers and reduction in the number of Purkinje cells in animals treated with a higher convulsive dose of paraoxon (1 mg/kg). In addition, exposure of rats to 1 mg/kg of paraoxon activated apoptosis pathway confirmed by an increase in Bax and caspase-3 and a decrease in Bcl-2 protein levels. According to our results, cerebellar histological changes and alterations in the expression of apoptosis-related proteins occur following exposure to a high convulsive dose of paraoxon and persist for a long time.